Exploring math anxious parents' emotional experience surrounding math homework-help. (2020) - DiStefano, Michela; O'Brien, Bronwyn; Storozuk, Andie; Ramirez, Gerardo; Maloney, Erin A.
Highlights: Higher-math-anxious parents report feeling more negative emotions during math homework-help. These relations are not due to differences in math ability or general anxiety. These findings have important implications for educational practices and policy. Abstract: In two separate studies, we examined the relation between parents' math anxiety and their perceptions of their math homework-helping interactions with their children. Specifically, we surveyed parents of children in Grades 1–6 across North America on the time they spend helping their child with their math homework and the level of confidence, conflict, stress, frustration, and emotionality that they feel during math homework interactions as a function of their math anxiety. As predicted, parents who were higher in math anxiety reported feeling a more negative emotional experience surrounding the homework environment when helping their child with math homework. Understanding this dynamic has important implications for educational practices, especially given the push for parents to be involved in their children's learning.